Surveillance and threat detection prevention versus mitigation - Kirchner, Richard, Jr (Butterworth-Heinemann, 2014)
Surveillance and Threat Detection offers readers a complete understanding of the terrorist/criminal cycle, and how to interrupt that cycle to prevent an attack. Terrorists and criminals often rely on pre-attack and pre-operational planning and surveillance activities that can last a period of weeks, months, or even years. Identifying and disrupting this surveillance is key to prevention of attacks. The systematic capture of suspicious events and the correlation of those events can reveal terrorist or criminal surveillance, allowing security professionals to employ appropriate